E-shopping: An Extended Technology Innovation - L., Ganesh; Agarwal, Varsha (Journal of Research in Marketing (ISSN: 2292-9355), 2014)
Online shopping is a new way in the world of retailing and future of ecommerce world definitely. A report by Avendus Capital in “India goes Digital” Indian ecommerce market was estimated at 28,500 Crore in 2011. According to Forrester, ecommerce market in India will grow fastest within Asia-Pacific region at a CAGR of 57% between years 2012-2016. Both single branded and multi branded companies are selling their products and services online. This increasing growth has generated the idea to conduct this study. In this context, research paper explores three factors that influence consumer intentions to purchase products online: safety oriented, convenience oriented and price oriented. The study analyzes the perception of 150 online shoppers in Bangalore regarding convenience, safety and price and their intention and attitude towards online shopping. A structured close ended questionnaire was administered to online shoppers. The collected data were analyzed in two stages. In the first stage correlation was performed to analyze between online shopping features and consumer purchase intention. In the second stage factor analysis was carried out to find the critical factors responsible for making consumer purchase intentions towards online shopping. The findings of this research shows that ‘safety’ produces trust, ‘convenience’ originates user friendliness and ‘price’ provides economy, all three influenced directly the attitude towards purchase intentions of consumers to shop online. This paper provides useful insight for the researchers to understand the consumer’s attitude towards online shopping intention.